Description of Coladenia simianensis sp. nov. (Lepidoptera: Hesperiidae) from China, with an annotated checklist of the genus Coladenia Moore, 1881 - Xue, Guo-Xi; Li, Xiao-Juan; Li, Ding-Kai (Zootaxa, 2017)
A new species, Coladenia simianensis sp. nov., is reported from Simian Mountain of Chongqing, China. Judging from the male genitalia, this new species resembles C. tanya Devyatkin, 2002, C. uemurai Huang, 2003 and C. motuoa Huang & Li, 2006, but can be distinguished from them by the following combination of characters: forewing discal spots are narrow and clearly separated; distal and dorsal branches of the valva are very long and strongly curved. A checklist of the species and subspecies of the genus Coladenia is provided, and some questionable distribution records in literature are corrected.